Prosedur Penerjemahan dalam Cerita Anak The Ugly Duckling (Translation Procedures in the Chlldren's Story The Ugly Duckling: A Qualitative Study) (Riwayat: Educational Journal of History and Humanities, 2026)
Perkembangan intelektual, emosional, dan sosial anak dapat ditingkatkan melalui pengenalan bahasa serta budaya. Terdapat berbagai jenis media pengenalan, salah satunya adalah beragam cerita untuk anak. Penelitian ini merupakan penelitian deskriptif kualitatif yang bertujuan untuk mengidentifikasi prosedur penerjemahan yang diterapkan dalam proses alih bahasa cerita anak The Ugly Duckling dari bahasa Inggris ke bahasa Indonesia. Data terdiri dari unit mikro, seperti kata, frasa, klausa, dan kalimat yang dianalisis menggunakan metode analisis teks. Analisis data pada penelitian ini menggunakan teori proses penerjemahan yang dikemukakan oleh Peter Newmark. Berdasarkan hasil penelitian, ada 8 prosedur penerjemahan dalam proses alih bahasa The Ugly Duckling, yaitu modulation (32%), descriptive equivalent (13%), cultural equivalent (13%), reduction (13%), expansion (11%), transpositions (11%), through-translation (5%), dan functional equivalent (3%).The intellectual, emotional, and social development of children can be enhanced through the introduction of language and culture. There are various types of introduction media, one of that is children's stories. This qualitative descriptive research aims to identify the translation procedures applied in the translation process of the children's story The Ugly Duckling from English into Indonesian. The data consist of micro units such as words, phrases, clauses, and sentences, analyzed using text analysis methods. The data analysis in this study employs the theory of translation procedures proposed by Peter Newmark. Based on the research findings, there are eight translation procedures used in the translation of The Ugly Duckling, namely modulation (32%), descriptive equivalent (13%), cultural equivalent (13%), reduction (13%), expansion (11%), transpositions (11%), through-translation (5%), and functional equivalent (3%).